Learning Strategies and Competency of AIKA Lecturers in Improving Students' Religious Insights at the University of Muhammadiyah Tangerang - masrizal masrizal (STAI Attanwir Bojonegoro, 2022)
The purpose of this study was to find out how far the results of the achievement of religious insight produced by the University of Muhammadiyah Tangerang to its students. This research was conducted using a qualitative method, namely by collecting data through library studies or Library research and AIKA Learning Strategies and Lecturer Competencies as research objects. that AIKA's Learning Strategy and Lecturer Competence are strategic factors as the driving force, and the main mission of organizing the University of Muhammadiyah Tangerang. The AIKA Education Strategy and Lecturer Competence are also the strengths of Universitas Muhammadiyah Tangerang because they can be the basis of spiritual, moral, and intellectual strength as well as the driving force for the entire academic community. and excel in science and technology as the embodiment of tajdid da'wah amar ma'ruf nahi munkar. This is one indicator of the achievement of the mission of organizing and managing the University of Muhammadiyah Tangerang. Improving the quality of processes and outcomes (outcomes) of AIKA's Education Strategy and Lecturer Competencies must be implemented continuously and systematically.